2000
DOI: 10.1292/jvms.62.539
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Fibrous Histiocytoma in a Djungarian Hamster

Abstract: ABSTRACT. A subcutaneous malignant fibrous histiocytoma (MFH) was observed in the region between the right posterior trunk and right hind limb of a 2-year-old male Djungarian hamster weighing 45 g. Histologically, the tumor consisted of bizarre multinucleated giant cells, histiocytic cells, and fibroblastic cells with a storiform pattern, and was considered to be of the storiform-pleomorphic type of MFH. Severe nuclear atypia with prominent nucleoli and many mitotic figures was also observed. Electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The malignant fibrous histiocytoma had histologic and immunophenotypic features similar to a previously described lesion in the subcutis of a 2-year-old Djungarian hamster. 9 It is possible that these two tumors were incidental findings associated with aging, and were not associated with chronic inflammation. However, the intra-abdominal site and predominant localization of the round cell sarcoma to the ICC junction suggests that the tumors may have emerged within an area of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The malignant fibrous histiocytoma had histologic and immunophenotypic features similar to a previously described lesion in the subcutis of a 2-year-old Djungarian hamster. 9 It is possible that these two tumors were incidental findings associated with aging, and were not associated with chronic inflammation. However, the intra-abdominal site and predominant localization of the round cell sarcoma to the ICC junction suggests that the tumors may have emerged within an area of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In Djungarian hamsters over 2 years old, the incidence of spontaneous neoplasia has been reported as 30% (Cantrell and Padovan, 1987). Reported spontaneous neoplasms included mammary carcinomas, cutaneous papillomas and squamous‐cell carcinomas, pulmonary adenomas and carcinomas, liver adenomas and carcinomas, lymphosarcomas, ovarian carcinoma, angiosarcoma, malignant fibrous histiocytoma and mastocytomas, but there have been fewer than 10 review articles or case reports on Djungarian hamster tumours (Pogosianz, 1975; Cantrell and Padovan, 1987; Harkness and Wagner, 1995; Endo et al., 2000; Nishizumi et al., 2000). As more Djungarian hamsters are used in biomedical research and owned as pets, more tumours will presumably be observed in this species.…”
Section: Discussionmentioning
confidence: 99%
“…However, incidences vary significantly from colony to colony (Harkness and Wagner, 1995). Djungarian hamsters are reported to develop tumours of the oral cavity, skin, mammary glands and subcutis (Pogosianz, 1975; Cantrell and Padovan, 1987; Harkness and Wagner, 1995; Endo et al., 2000; Nishizumi et al., 2000).…”
Section: Introductionmentioning
confidence: 99%